A comparative study of the impact of civil war on local political society in medieval and early modern Hampshire - Lynch, Lucy (2016)
This thesis of 65,903 words offers a comparative study examining the impact of civil war on local political society in medieval and early modern Hampshire, namely the Wars of the Roses (1450-85) and the English Civil Wars (1640-1660). The comparative methodology employed here seeks to detect both contrasts and comparisons between the two periods with the intention of furthering our understanding of how civil war affected local society in pre-industrial England. In so doing, this thesis will explore the makeup of local society within Hampshire, discussing both the offices and the personnel who filled them; the relationships that existed between the local officers themselves and with central government, by examining concepts such as loyalty and allegiance (both to the locality and to central government), political and religious ideology and local independence.